2016
DOI: 10.1111/tmi.12670
|View full text |Cite
|
Sign up to set email alerts
|

Caring for patients with rabies in developing countries – the neglected importance of palliative care

Abstract: SummaryAlthough limited publications address clinical management of symptomatic patients with rabies in intensive care units, the overwhelming majority of human rabies cases occur in the rural setting of developing countries where healthcare workers are few, lack training and drugs. Based on our experience, we suggest how clinicians in resource-limited settings can make best use of essential drugs to provide assistance to patients with rabies and their families, at no risk to themselves. Comprehensive and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Another five (16,22,(24)(25)(26) articles mentioned cancer, but not in isolation, they also pointed out other diseases such as diabetes, Alzheimer's disease, as well as respiratory and cardiovascular diseases. The expansion of PCs to other diseases appeared in a study on human rabies and suggested a review of clinical guidelines, proposing the introduction of PCs for people with rabies in endemic countries (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Another five (16,22,(24)(25)(26) articles mentioned cancer, but not in isolation, they also pointed out other diseases such as diabetes, Alzheimer's disease, as well as respiratory and cardiovascular diseases. The expansion of PCs to other diseases appeared in a study on human rabies and suggested a review of clinical guidelines, proposing the introduction of PCs for people with rabies in endemic countries (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite repeated attempts to treat rabies encephalitis, there is a lack of easily applicable palliative care protocol for rabies patients, which could be used in a developing country. Tarantola et al 18 recently published detailed suggestions on palliative treatment of rabies which could be used in a resource-limited setting. The authors explain palliative treatment of various symptoms of rabies, dosages of drugs, alternative routes of delivery, and also address nursing care concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a fatal condition, it is important to avoid depressing respiration by giving the diazepam too rapidly by iv injection. Diazepam will alleviate the patient’s suffering, while giving the family time to adjust and consider the possibility of taking them home to die, if that is their personal or cultural preference [ 32 ]. This can be achieved by giving a slow injection (0.5 ml/min, which is 2.5 mg/min) of diazepam.…”
Section: Care Of Patients With Confirmed Rabies Encephalomyelitismentioning
confidence: 99%